Peran Sektor Pasar Di Desa Sungai Salak Dalam Pemulihan ‎Ekonomi Masyarakat Pasca Pandemi Covid-19‎ - Syahfitri, Triyana; Fauziah, Indah; Yusri, Muhammad Nazipul; Fatimah, Sitti (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2023)
Empowerment of traditional markets in Sungai Salak serves to improve people's welfare. In this case the Government must develop this market, because the economic activities of the Salak River are in this market. the government must carry out development both in terms of infrastructure and basic needs of traditional markets. Because it is feared that after Covid 19, traditional markets will disappear to be replaced by modern markets and online markets, even though these traditional markets are one that can revive the community's economy after the economic downturn due to the Covid 19 pandemic that occurred. it is a big responsibility for the government to be developed, because traditional markets are now competing with modern markets. Of course, the development of traditional markets requires the right strategy from the government.